Making Fast-Track Surgery Transportable: Sino-Danish Travel Work. Issue 3 (3rd July 2021) - Andersen, Signe Lindgård
Abstract: This article examines the concrete travel work that enables the global transport of Fast-Track Surgery (FTS), a set of evidence-based, standardized protocols and guidelines for perioperative recovery. Having ethnographically followed FTS training for medical staff from provincial hospitals in China's Gansu province at a local hospital in Denmark, I show how FTS is made transportable through interactions between Chinese and Danish healthcare professionals in a series of workshops, meetings and educational activities. I argue that the transportability of a health-promoting infrastructure like FTS is neither a matter of technology transfer nor of evidence as such. Rather, it requires a specific kind of travel work in the form of traveling comparisons as a constant two-way dynamic between hospital settings in Denmark and China.